2003
DOI: 10.1002/anie.200352817
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Methane and Ammonia by Dinuclear Bimetallic Platinum–Coinage‐Metal Cations PtM+

Abstract: The activation and functionalization of methane constitute continuing challenges for catalysis. One example of their industrial realization is given by the Degussa process for the large-scale production of hydrogen cyanide from methane and ammonia using platinum as heterogeneous catalyst [Eq. (1)].Our aim is the development of a gas-phase model for this process that may enhance the current mechanistic knowledge [1,2] and thus ultimately contribute to rational catalyst improvement. So far, atomic Pt + , homonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 29 publications
2
33
0
2
Order By: Relevance
“…Previous quantum chemical calculations have found very strong d-sp mixing for Au, and the UPS spectra of the pure Au cluster anions also agree with these calculations [60,[79][80][81][82]. The stronger d characters of Au nanoclusters are most likely related to relativistic effects [83][84][85]. As the atomic nuclear charge increases, electrons penetrating to the nucleus increase their velocity, and consequently their mass due to relativity.…”
Section: Reactivity Measurementssupporting
confidence: 73%
See 1 more Smart Citation
“…Previous quantum chemical calculations have found very strong d-sp mixing for Au, and the UPS spectra of the pure Au cluster anions also agree with these calculations [60,[79][80][81][82]. The stronger d characters of Au nanoclusters are most likely related to relativistic effects [83][84][85]. As the atomic nuclear charge increases, electrons penetrating to the nucleus increase their velocity, and consequently their mass due to relativity.…”
Section: Reactivity Measurementssupporting
confidence: 73%
“…The relativistic effect causes the s electrons to be in smaller orbitals than one might classically expect. The s electrons are therefore more strongly bound, shielding d electrons more effectively [83][84][85]. Ample evidence can be found in the literature that the relativistic effect plays a pivotal role in the chemistry of heavy metal atoms like Au [83,85].…”
Section: Reactivity Measurementsmentioning
confidence: 96%
“…Theoretical methods are meanwhile even able to address systems as complex as mixed transition-metal clusters. Thus, experimental investigations of methane activation by heteronuclear Pt m M n + cluster cations (M = Cu, Ag, Au) and the subsequent coupling reactions with gaseous ammonia [237][238][239] were rapidly followed by detailed theoretical studies of the bare metal clusters themselves, the products formed with methane, and the subsequent reaction with NH 3 , which provided a reasonable basis for understanding all of effects observed experimentally [240][241][242][243][244] -a remarkable performance of theory in almost incredibly short time!…”
Section: Gas-phase Reactions Of Coinage-metal Cluster Ionsmentioning
confidence: 98%
“…Cationic Au-Pt clusters have shown unique reactivity for C-N coupling of methane and ammonia. 11,12 Recently it has been reported that carbon-supported Au-Pt bimetallic NPs display performances better or similar to those of pure platinum supported on carbon for oxygen reduction, 13,14 provided alloyed and not phasesegregated Au-Pt NPs are used. It has been also shown that platinum could be partially substituted by gold for application in methanol oxidation: higher resistance to poisoning was observed in acidic media with Au-Pt bimetallic NPs, while in alkaline environment a significant overall improvement in performance was reported.…”
Section: Introductionmentioning
confidence: 99%